Research on desiliconization of brown corundum fly dust and bauxite based on roasting-alkali leaching method - Nian Liu; Chaoyi Chen; Junqi Li; Dong Liang (PLoS ONE, 2025)
The raw material for smelting brown corundum is high-quality bauxite. As the quality of bauxite decreases, the main impurity, silicon content, increases, which affects the product quality and smelting energy consumption. Additionally, the smelting process produces a significant amount of brown corundum fly dust (BCFD) with a low utilization rate, resulting in resource wastage. In order to utilize low-quality bauxite and BCFD, this article proposes the method of “roasting-alkali leaching.” Through mixed desilication, the impact of alkali leaching factors on desilication is investigated, analyzed the desiliconization mechanism of BCFD, and established the kinetics of the desilication reaction. Results indicated that the optimal conditions for mixed desilication are BCFD/bauxite mass ratio of 1:6, desilication temperature of 95°C, desilication time of 30 min, alkali concentration of 110 g/L, and liquid-solid ratio of 10:1, achieving a desilication rate of 60.90%. The Al-Si ratio (A/S) of the concentrate increases from 5.33 to 11.72, meeting the requirements for brown corundum smelting raw materials. The desilication reaction follows a solid shrinkage core model, with a kinetic equation of 1−2/3α−(1−α)2/3 = 15.50exp[−29299/(RT)]·t, and an apparent activation energy of 29.30 kJ/mol. The synergistic mechanism involves fine particles of the BCFD adsorbing on the surface after mixing with the bauxite, increasing the mineral surface area and the activity of silicon, thereby accelerating the reaction rate.